The relevance between water release behavior and pore evolution of hard lignite during the thermal-drying process. Issue 6 (December 2019) - He, Qiongqiong; Li, Xinyuan; Miao, Zhenyong; Huang, Shaomeng; Wan, Keji
Abstract: As known, the shrinkage of coal and the pore collapsed during the drying process due to water removal. The relevance between water release behavior and pore evolution of lignite during the thermal-drying process was studied in this work. From N2 adsorption of traditional pretreated samples and freezing wet samples, most of moisture was in the pores in the range of 26–100 nm, and results from low-field nuclear magnetic resonance (LFNMR) confirmed this conclusion that the removed moisture was in the pores with pore size smaller than 200 nm, while from the mercury intrusion porosemitry (MIP) results, the most obvious reduction of macropores was in the range of pore dimeter larger than 1 μm and there was almost no change of pore volume in the range of pore diameter smaller than 200 nm, which was completely different from traditional ideas that the pore shrunk or collapsed due to water removed. The macropores were more prone to collapse than mesopores and micropores, maybe due to its structural mechanical characteristics. And the effect of pore evolution on moisture release behavior was related to the specific drying methods and mass transfer processes. Highlights: Most of moisture in the lignite pores was in the range of 26–100 nm. Obvious reduction of pore volume was in the range of pore dimeter larger than 1 μm. Almost no change of pore volume in the range of pore diameter smaller than 200 nm. The macropores collapse might be due to its structural mechanical characteristics.